2010
DOI: 10.1042/cs20100113
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone attenuates development of polycystic kidney disease and prolongs survival in Han:SPRD rats

Abstract: Although pioglitazone, a PPAR-gamma (peroxisome-proliferator-activated receptor-gamma) agonist, has been shown to prolong survival in two rapidly progressive pkd1 (polycystic kidney disease 1)-knockout mice models through disparate mechanisms, these studies lacked data on therapeutic potential and long-term safety because of a short observation period. In the present study, we have used another potent PPAR-gamma agonist, rosiglitazone, to treat Han:SPRD rats, a slowly progressive ADPKD (autosomal dominant PKD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…More recent studies have shown a survival benefit in conditional (principal cell) Pkd1 null mice associated with a reduction in systemic blood pressure (but without an effect on cyst formation) and Han:SPRD rats, with a moderate effect on kidney and liver cyst volumes in female Pck rats (2,6,25). Nonetheless, the mechanism of these reported effects remains unclear, with one study reporting no effect on cell proliferation or apoptosis, another reporting reductions in the expression of profibrotic [transforming growth factor (TGF)-␤1] and inflammatory (MCP-1) cytokines and Wnt (␤-catenin) signaling, and finally decreased CFTR expression by cyst epithelia (and thus Cl Ϫ secretion) (2,6,25).…”
mentioning
confidence: 99%
“…More recent studies have shown a survival benefit in conditional (principal cell) Pkd1 null mice associated with a reduction in systemic blood pressure (but without an effect on cyst formation) and Han:SPRD rats, with a moderate effect on kidney and liver cyst volumes in female Pck rats (2,6,25). Nonetheless, the mechanism of these reported effects remains unclear, with one study reporting no effect on cell proliferation or apoptosis, another reporting reductions in the expression of profibrotic [transforming growth factor (TGF)-␤1] and inflammatory (MCP-1) cytokines and Wnt (␤-catenin) signaling, and finally decreased CFTR expression by cyst epithelia (and thus Cl Ϫ secretion) (2,6,25).…”
mentioning
confidence: 99%
“…TZDs have been used for the treatment of Type 2 diabetes mellitus (T2DM) because of their good safety during long-term clinical processes for the improvement of renal functions (36). TGF-β1 and MCP-1 expression was suppressed and kidney fibrosis volume and inflammatory cell infiltration were reduced by rosiglitazone treatment in PKD, as was also the case in T2DM disease (33). More recently, the novel PPAR-γ agonist known as alpha-aryloxy-alpha-methylhydrocinnamic acid derivatives, DH9 also had anti-proliferative effects on PKD (37).…”
Section: Novel Therapeutic Approaches In Pkd Therapeutic Target: Ppar-γmentioning
confidence: 91%
“…This study was conducted with the expectation that PPAR-γ agonists would attenuate cell proliferation via the checking of cell cycle molecules including PCNA, phosphorylated-Rb, and cyclin D1 and D2 (31). In a recent study, the administration of rosiglitazone was shown to attenuate cyst development and protect renal function via measurements of Blood Urea Nitrogen (BUN) and Creatinine (Cr) in a typical PKD animal model, namely the Han:SPRD rat (33). Additionally, rosiglitazone-treated Cy/+ Han:SPRD rats evidenced longer survival durations than control rats (33).…”
Section: Novel Therapeutic Approaches In Pkd Therapeutic Target: Ppar-γmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule inhibitors of CFTR inhibited the development of PKD in a rodent model [65,66]. PPAR-gamma activators have been shown to inhibit vasopressin mediated chloride transport via CFTR [67] and have been shown to inhibit renal cystic disease in rat models of PKD [68][69][70]. Interestingly, renal cystic disease appears to be less severe in humans who inherited both ADPKD and cystic fibrosis [71,72] further implicating the CFTR chloride channel in the secretion of cyst fluid and contributing to the progression of PKD.…”
Section: Human Trialsmentioning
confidence: 99%